Disclosing Physician Ratings: Performance Effects and the Difficulty of Altering Ratings Consensus - EYRING, HENRY (Journal of Accounting Research, 2020)
ABSTRACT I examine effects of a health care system's policy to publicly disclose patient ratings of its physicians. I find evidence that this policy leads to performance improvement by the disclosed, subjective ratings and also by undisclosed, objective measures of quality. These effects are consistent with multitasking theory, in that physicians respond to the disclosure by providing more of a shared input—time with patients—that benefits performance by ratings and underlying quality. I also find, as predicted by information cascade theory, that the ratings become jammed to some degree near initially disclosed values. Specifically, raters observe the pattern of initial ratings and follow suit by providing similar ratings. Finally, I find evidence that physicians anticipate rating jamming and so concentrate their effort on earlier performance in order to set a pattern of high ratings that later ratings follow. These results demonstrate that the disclosure of subjective ratings can benefit performance broadly but can also shift effort toward earlier performance.